De Novo and Divergent Synthesis of Highly Functionalized Furans by Cascade Reactions of 2‐Hydroxy‐1, 4‐diones with Nucleophiles. Issue 16 (22nd February 2021) - Liu, Hai‐xuan; Ji, Fei; Chen, Yu; Gao, Ya; Wang, Jun‐ke; Zhang, Ming‐zhi; Liu, Fang; Sha, Qiang
Abstract: Herein, a divergent synthesis of a variety of 2α‐ and 5α‐substituted furan derivatives from 2‐hydroxy‐1, 4‐diones is reported. By using appropriate substrates and an acid catalyst, the reactions occurred selectively through cyclization/1, 6‐conjugate addition or cyclization/Friedel–Crafts‐type cascade reactions. A broad range of nucleophilic reagents (>10 types for the 1, 6‐conjugate addition for 5α substitution and >20 types for the Friedel–Crafts‐type cascade reaction for 2α substitution), including alcohols, amides, furan, thiophene, pyrrole, indole, phenols, and many others, can successfully participate in the reactions, providing a universal strategy for a diversity‐oriented synthesis of α‐substituted furan derivatives. Deuteriation experiments and DFT calculations were carried out to support the proposed reaction mechanisms. Antifungal activity experiments revealed that products with an indole or 4‐hydroxycoumarin core substituted at the 2α position showed moderate activities against Rhizoctorzia solani and Botrytis cinerea, respectively. Abstract : Great selection ! We present herein a de novo and divergent synthesis of 2α‐ and 5α‐substituted furans from 2‐hydroxy‐1, 4‐diones and a variety of nucleophiles with good regio‐ and chemoselectivity, as well as a very broad substrate scope (>10 types of nucleophiles for the 5α functionalization and >20 types of nucleophiles for the 2α functionalization; see scheme). The products show good potential as antifungal agents.